Nicoletta Momigliano, In Search of the Labyrinth. The Cultural Legacy of Minoan Crete. - Gallou, Chrysanthi (Journal of Greek Archaeology, 2022)
Nicoletta Momigliano, In Search of the Labyrinth. The Cultural Legacy of Minoan Crete. pp. xvi +362, 83 b/w ills. London and New York: Bloomsbury Academic, 2020. ISBN 978-1-7845-38545, hardcover £70; 978-1-350-15670-8, paperback £20; E-book 978-1-35015-672-2, £18.